Targeted review of IL36RN mutations in patients with generalised pustular psoriasis - James G. Krueger; Anna Pagotto; Samuel Haftel; Birgit Gradl (Wiley, 2024)
Abstract Background Generalised pustular psoriasis (GPP) is a rare and chronic skin disease historically treated with therapies that were originally intended to treat plaque psoriasis (PsO). However, GPP and plaque PsO have distinct pathogeneses and clinical courses. Objectives This study aimed to further characterise the unique genetic background of GPP by summarising evidence on the frequency and type of IL36RN gene mutation, a gene that normally suppresses proinflammatory responses, in patients with GPP compared to patients with GPP and plaque PsO, and patients with plaque PsO only. Methods and Results A targeted literature review was conducted to identify studies reporting IL36RN mutations and/or HLA‐Cw6 allele frequency in patients with GPP. Meta‐analyses showed a significantly higher rate of IL36RN mutations in the GPP‐only population compared to the GPP + plaque PsO population (OR 3.51; 95% CI 2.29, 5.38). Monoallelic mutations of IL36RN were found in up to 33.3%, and biallelic mutations in up to 73.2% of patients with GPP (GPP‐only and GPP + plaque PsO), in contrast with mono‐ and biallelic frequencies of only 0%-11.9% and 0%, respectively, in patients with plaque PsO only. Mean age‐of‐onset ranged from 5.9 to 48.9 years old, with most studies reporting a GPP age‐of‐onset between 20 and 40 years old. Twenty‐one mutations were identified in the biallelic state and three in monoallelic. The most reported mutations were c.115 + 6T > C (p. Arg10ArgfsX1) (18 studies); c.227 C > T (p.Pro76Leu) (10 studies); and c.338 C > T (p.Ser113Leu) (8 studies). Mutations varied depending on geography and ethnicity, with the most frequently reported mutation predominantly reported in East Asian studies and international studies that included Asian patients. Rates of HLA‐Cw6, the risk allele most strongly associated with plaque PsO, were 0%-28.6% for patients with GPP, similar to rates in the general population (10.5%-20%). Conclusion Considering the differences between GPP and plaque PsO in aetiology and disease symptoms, effective, GPP‐specific treatment options are needed, and recent research suggests that blockade of IL‐36 signalling may be an effective target for treatment of GPP.